The Role of 6-Minute Walk Test Guided by Impedance Cardiography in the Rehabilitation Following Knee Arthroplasty: A Randomized Controlled Trial - Lin, Yangyang; Hu, Xingwei; Cao, Yalin; Wang, Xing; Tong, Yao; Yao, Fengjuan; Wu, Peihui; Huang, Huiling (Frontiers in Cardiovascular Medicine, 2021)
Objective: To explore the effect of the 6-minute walk test (6MWT) guided by non-invasive cardiac output on the rehabilitation of patients with knee osteoarthritis following artificial total knee arthroplasty. Methods: About 66 patients with knee osteoarthritis planned to undergo artificial total knee arthroplasty were included from March 2019 to October 2019, and randomly assigned to the intervention group or control group. Under the guidance of a clinical rehabilitation physician, orthopedic physician, and cardiologist, a home rehabilitation exercise program based on 6MWT and non-invasive cardiac output was formulated for patients with knee osteoarthritis. The participants of the intervention group conducted full rehabilitation training supervision and guidance through the WeChat platform to ensure their rehabilitation pieces of training were completed safely and effectively. As for the control group, patients were just given rehabilitation training manuals at the time of discharge and completed the training by themselves. Results: At 6 months post-operatively, 6-minute walk distance (413.88 ± 44.61 vs. 375.00 ± 40.53 m, P < 0.05), active metabolic equivalent (4.13 ± 0.29 vs. 3.88 ± 0.27, P < 0.05), stroke volume after 6MWT (114.97 ± 12.05 vs. 98.38 ± 16.43 ml, P < 0.05), and cardiac output (11.92 ± 1.68 vs. 9.79 ± 1.82 l/min, P < 0.05) of the intervention group were significantly higher than those of the control group. The symptom evaluation scores of the intervention group were also better than those of the control group. Conclusions: The multidisciplinary post-operative rehabilitation exercise training program is beneficial to the recovery of lower limb function and the improvement of exercise capacity after knee replacement, and it also helps to improve the non-invasive hemodynamic indicators related to the cardiac function of the patient. Clinical Trial Registration:http://www.chictr.org.cn/index.aspx.